Leaf Blight: A New Disease of Xanthium strumarium Caused by Exserohilum rostratum in Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
The fungus Exserohilum rostratum was consistently isolated from necroticspots and blight of Xanthium strumarium leaves. It was identified on the basis ofmicroscopic and macroscopic characters. Pathogenecity was demonstrated bypressurized hand sprayer inoculation. This is the first record of leaf blight caused by E.rostratum on X. strumarium in Sudan